Penilaian Pembelajaran Pendidikan Agama Islam Dalam Kurikulum KTSP Di SMP Negeri 1 Mojosongo Boyolali Tahun Pelajaran 2015/2016 - Qomariyah, Nur Dwi; , Drs. Najmuddin Zuhdi, M.Ag (2017)
Assessment is a series of activities to obtain, analyze, and interpret data on the process and learning output of students which is conducted systematically and continuously so that the data become meaningful information in taking decision. In learning the Islamic education (PAI), SMP Negeri 1 Mojosongo State Yunior High School uses an assessment in the curriculum Based on EducationalUnit Strate (KTSP). Based on the background, this research aims to know the implementation of learning assessment of Islamic education (PAI) in the curriculum based KTSP in SMP Negeri 1 Mojosongo Boyolali in the academic year of 2015/2016. The benefit of this research is as the corpus of knowledge especially on the learning assessment of Islamic education in the curriculum of KTSP. This research is a field research using data sources from the teachers of Islamic education (PAI) and documents of SMP Negeri 1 Mojosongo Boyolali. The method of data collection uses documentation, observation and interview. Meanwhile, the method analysis of data analysis uses the descriptive analysis approach. Based on the research and data analysis, it can be concluded that thelearning assessment of Islamic education in the curriculum of KTSP has been categorized as good criterion. It is proven by the average of implementation of assessment which has reached 67.2%. Meanwhile, the supporting factors are: the presence of approach between the teacher and the students and the students are positioned as playing peers as well as students. Meanwhile, the inhibiting factor is that not all students do not memorize the hijaiyah letters so that there is still difficulty in reading article Arabic.